STUDI KASUS IMPLEMENTASI GERAKAN ORANG TUA MEMBACAKAN BUKU DALAM MENDUKUNG KEMAMPUAN BAHASA ANAK USIA 5–6 TAHUN DI TK BILINGUAL ISLAMIC SCHOOL RUMAH ILMU BEKASI - Nandini, Oktavia; Yossi Srianita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study describes the implementation of the Parents Reading Books Movement and its role in supporting the language development of children aged five to six years at Rumah Ilmu Bilingual Islamic Kindergarten, Bekasi. A qualitative case-study design was employed. Participants were selected purposively and consisted of the school principal, one Group B teacher, ten parents, and ten children. Data were collected through observation, semi-structured interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing, while credibility was strengthened through source and technique triangulation. The findings show that the program was implemented through planning, home-based reading activities, school monitoring, and periodic evaluation. Parents generally read for 10–20 minutes per session during a two-week period each month and involved children in discussing characters, story sequences, and messages. Teachers and parents reported observable development in listening, speaking confidence, vocabulary use, answering questions, and retelling stories. The program was supported by school commitment, age-appropriate books, parent–teacher cooperation, children’s enthusiasm, and routine monitoring. Its implementation was constrained by parents’ work schedules, differences in reading techniques, limited weekday interaction, and fluctuating child interest. The movement therefore functioned as a practical home–school literacy program, although the findings should be interpreted within the limits of a single qualitative case without standardized pre- and post-measurement.